Consumo de minerais e risco cardiovascular em população de mulheres de comunidades carentes de Maceió/AL - Silva , Priscilla Maria Bernardo da (2015)
OBJECTIVE: To evaluate the mineral intake and its relationship with cardiovascular risk in a population of adult women from poor communities in the city of Maceió / AL. METHODS: A cross-sectional study with a sample of 67 women aged between 19 and 45 years. Socioeconomic and demographic data were collected. Anthropometric measurements were collected, food consumption through the 24 hour recall, biochemical evaluation. The data was entered in "Epi - info". The statistical analysis was carried out with the help of "SPSS". Normality was assessed using the Liliefors test and homogeneity by the Levene test. Subsequently, the statistical inference was performed with the application of the "t" test and Pearson's correlation, considering the differences or associations as statistically significant when p0,05. RESULTS: It was verified that the majority of women (83.3%) were housewives and the majority had monthly family income between ½ and 1 minimum wage and 76.2% were sedentary. Regarding nutritional status, 71.6% of the women were overweight and obese and 60% had a waist circumference greater than 0.80 cm. Biochemical data revealed normal glycemia in 97.6% of the sample, about 40% presented high cholesterol and LDLc levels, 7.6% presented elevation in triglycerides. The consumption of minerals associated with cardiovascular risk was inadequate for all, except sodium and zinc. CONCLUSION: There is a high prevalence of overweight in this population, in addition to presenting other risk factors, such as dyslipidemias and current food consumption data, where they presented inadequate intake of minerals that are associated as a protection factor for diseases Cardiovascular diseases.